Analysis of Profitability in Mining Companies Affiliated with MIND ID in 2020 - 2023 - Ningrum, Retno Widya; Pramayuda, Agung; Musadat, Irfan Achmad (Indonesian Scientific Publication, 2025)
MIND ID (Mining Industry Indonesia) is a holding company that aims to manage and oversee State-Owned Enterprises (SOEs) mining companies. This holding is expected to play a role in managing the nation's strategic assets and enhancing value through synergy and efficiency among the mining companies under MIND ID. Three of these companies, namely PT Aneka Tambang Tbk, PT Bukit Asam Tbk, and PT Timah Tbk, have listed their shares on the Indonesia Stock Exchange, with the stock codes ANTM, PTBA, and TINS, respectively. As an investor, it is crucial to monitor the performance of companies in which one is considering investment or has already invested, particularly from the financial perspective, especially profitability. Based on profitability analysis using Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE), PTBA stands out as the top-performing company, with an overall rating of